RNA‐binding proteins in diabetic microangiopathy. Issue 5 (6th April 2022) - Tu, Chao; Wang, Liangzhi; Wei, Lan
Abstract: Background: As the most common complication of diabetes, the diabetic microangiopathy characterizes diabetic retinopathy (DR) and nephropathy (DN). Diabetic microangiopathy has always been a serious clinical problem. A wide variety of nucleic acid interacting factors called the RNA binding proteins (RBPS) take part in several crucial cellular processes. Methods: Over the past decade, studies have shown that RBPs have crucial part in both malignant tumors and diabetes, especially in diabetic microangiopathy. This review examined the research history of RBPS in DR and DN. Results: We reviewed the literature and found that RBPS is potentially useful as therapeutic targets, diagnostic markers, or predict disease progression. Conclusion: HuR acts as a vital therapeutic targeting protein in diabetic microangiopathy. IGF2BP2, P311, TTP, YBX1, and MBNL1 have a potential role in the treatment of DN. Abstract : RNA‐binding proteins: An emerging research directions of diabetic microangiopathy.